PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PT. ADHI KARYA, Tbk Periode 2015-2022 - Agustinar tina; Amalia Rahmawati; Fahriansah Fahriansah (Fakultas Ekonomi Universitas Samudra, 2023)
Stock price is the most important indicator in assessing the successful management of a company. If the company's achievements are good, investors orpotential investors will be interested in buying the company's shares. The problemof this research is the stock price at PT. Adhi Karya Tbk experienced fluctuationsfrom 2015-2022. This study aims to determine, describe, and analyze the effect of financial performance as measured by profitability ratios, namely Return On Assets (ROA), solvency ratios, namely Debt to Equity Ratio (DER) and activityratios, namely Total Asset Trunover (TATO) partially or simultaneously. to the share price at PT. Adhi Karya Tbk. This type of research is aquantitative research, the data source used is secondary data taken through the company website www.adhikarya.co.id with time series data in quarterly from of 32 samples. This research uses SPSS version 25 software. Partial research resultsshow that Return On Assets (ROA) has no effect on stock prices as evidenced bythe value of tcount< ttablewhich is 0.155 < 2.051 and the Debt to Equity Ratio (DER) has an effect on stock prices as evidenced with a value of tcount> ttable,namely -4.467 > 2.051 and Total Asset Trunover (TATO) has no effect on stockprices as evidenced by the value of tcount< ttable, namely -0.073 < 2.051. While theresults of the study simultaneously Return On Assets (ROA), Debt to Equity Ratio (DER) and Total Asset Trunover (TATO) affect stock prices with a value of Fcount > Ftable, namely 9.845 >2.96.